2010
DOI: 10.1097/nmc.0b013e3181d9c6d6
|View full text |Cite
|
Sign up to set email alerts
|

Patient Education to Reduce Elective Labor Inductions

Abstract: Education regarding elective induction offered during prepared childbirth classes was associated with a decreased rate among nulliparous women who attended classes when compared to those who did not attend. Patient education may be beneficial in reducing elective inductions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…There is some empirical evidence that pregnant women who received prenatal education that specifically informed them about risks associated with elective inductions had lower rates of inductions compared to women who did not receive this component of prenatal education (Simpson, Newman, & Chirino, 2010). Although these findings are hopeful, it must be acknowledged that childbirth educators face many obstacles (Lothian, 2007;Morton & Hsu, 2010).…”
Section: Implications For Practicementioning
confidence: 82%
“…There is some empirical evidence that pregnant women who received prenatal education that specifically informed them about risks associated with elective inductions had lower rates of inductions compared to women who did not receive this component of prenatal education (Simpson, Newman, & Chirino, 2010). Although these findings are hopeful, it must be acknowledged that childbirth educators face many obstacles (Lothian, 2007;Morton & Hsu, 2010).…”
Section: Implications For Practicementioning
confidence: 82%
“…In addition, Hodnett et al [27] asserts that the provision of information may reduce women's anxieties regarding impending labour. It therefore follows that adequate provision of information regarding inpatient cervical ripening would likely be of benefit to women and may reduce anxiety [7,12,14,15,27,30].…”
Section: Discussionmentioning
confidence: 98%
“…O'Brien et al [7] also reported that participants had "no idea" regarding the procedure of cervical ripening. A study by Rice-Simpson et al [30], in the United States, evaluated whether education classes would reduce the rate of women requesting elective labour induction. As pointed out by Jay [31] findings from the study by Rice-Simpson et al [30] suggests that the provision of information in the antenatal period had a positive impact on women's knowledge of labour induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the randomized controlled trial cited earlier (Simpson et al, 2010a(Simpson et al, , 2010b, 75% of the women who completed the survey and had an elective induction indicated that the physician suggested the option, compared to only 25% who indicated that they asked the physician to perform an elective induction.…”
Section: What Can Other Birth Professionals Do To Encourage Women To mentioning
confidence: 99%